2013
DOI: 10.4238/2013.december.19.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE polymorphisms and other risk factors on the severity of coronary artery disease

Abstract: ABSTRACT. Coronary artery disease (CAD) is a multifactorial disease influenced by genetic and environmental factors. Major risk factors of CAD are hypertension, hyperlipidemia, smoking, family history and obesity. Also polymorphisms in the angiotensin-I converting enzyme (ACE) gene can associate with CAD. The relationship between ACE polymorphisms and other risk factors is not well understood in CAD, likely due to the complex interrelation of genetic and environmental risk factors. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
4
29
0
2
Order By: Relevance
“…Our findings showed that LDL and TG are closely related to ACE I/D, β-Fg-455 A/G, and PAI-1 4G/5G, consistenting with the results of Li [51] and Guney et al [52]. In addition, our results displayed that hyperlipidemia is correlated with D allele of ACE I/D gene, which was confirmed by Suzuki et al and There are certain limitations in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that LDL and TG are closely related to ACE I/D, β-Fg-455 A/G, and PAI-1 4G/5G, consistenting with the results of Li [51] and Guney et al [52]. In addition, our results displayed that hyperlipidemia is correlated with D allele of ACE I/D gene, which was confirmed by Suzuki et al and There are certain limitations in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…For genotype II, in the comparison between the patients and controls, no statistical relevance was identified with a high power in any coronary risk factor. This demonstrates that the participation of these genotypes in the genesis of CAD is determined by more complex associations than other studies have indicated when analysing the genotypes as part of a single sample [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 64%
“…Возможно, вклад данного маркера в развитие сосудистых осложнений при СД2 не столь значим вследствие большей много-факторности поражения при данном типе заболевания. Также имеются сведения об ассоциации полиморфного маркера I/D гена ACE с нарушением ФЭ: у носителей генотипа DD выявлены достоверно большие толщина интима-медиа и распространенность атеросклероза по сравнению с пациентами с генотипами II и ID [15]. Однако зависимости динамики показателей ФЭ от рас-пределения генотипов маркера I/D гена ACE на терапии статинами у пациентов с СД2 в нашем исследовании вы-явлено не было.…”
Section: Discussionunclassified